What's New in the Field Of AMD? - Gábor Márk Somfai (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
As society ages, the importance of age-related eye diseases such as age-related macular degeneration (AMD) increases. The intravitreal treatment of neovascular AMD (nAMD), which accounts for about 10% of all AMD cases, revolutionized the world of ophthalmology about 15 years ago. This form of therapy, which can be used to treat - in addition to nAMD - other vascular retinal diseases, has led to a significant reduction in the incidence of vision loss and blindness caused by AMD and diabetes worldwide. Current developments in ophthalmology may shape the future of AMD treatment and include advancements in home-monitoring technologies like simpler, more cost-effective optical coherence tomography (OCT) devices, application of artificial intelligence for more detailed OCT, development and approval of novel therapeutics with longer-lasting effects on the eye or new mechanisms of action as well as new application systems using nanotechnological “Sustained-Delivery Systems” or suprachoroidal treatment with viral vectors for gene therapy. Overall, these exciting ongoing developments will change the treatment landscape in AMD and pave the way to increased quality of life for our elderly patients. Moreover, home monitoring technologies will ease the burden on our healthcare systems. At the same time, novel therapeutic options that require intravitreal surgical interventions may increase it.